An overview of the roles and responsibilities of Chinese medical colleges in body donation programs. Issue 4 (12th November 2013) - Zhang, Luqing; Xiao, Ming; Gu, Mufeng; Zhang, Yongjie; Jin, Jianliang; Ding, Jiong
<x xml:space="preserve">Abstract</x> The use of human tissue is critical for gross anatomy education in the health professions. Chinese medical colleges have faced a shortage of anatomical specimens over the past decade. While body donation plays an important role in overcoming this gap, this practice has only recently been introduced in China, and the donation rate is relatively low and fraught with a number of difficulties. In the past, traditional Chinese culture focused on preserving the human body intact, which often limited body donation. In recent years, the public has become more open toward body donation. At Nanjing Medical University, only 20 bodies were donated in 2001. After the university became involved in an organized body donation program, this number increased to 70 donated bodies per year (2007 to 2012). This article describes and reviews Chinese medical colleges as a special case study among body donation programs, particularly in terms of the multiple responsibilities and roles that such institutions must assume in the course of adopting these programs. Medical colleges in China must serve as advocates, coordinators, builders, managers, educators, and beneficiaries in undertaking body donation programs. It is important for medical colleges to recognize these pluripotent roles and educate the public in order to promote body donation programs. This case study may also effectively guide and encourage Chinese medical colleges in refining their own body donation programs in the future. Anat Sci Educ 7: 312–320. © 2013 American Association of Anatomists.